The Effect of Polysorbate and Lecithin Surfactants in Cooking Oil Lubricants on Engine Temperature and Power - Rifqi Aditya; Haris Puspito (Evrimata: Journal of Mechanical Engineering, 2025)
Lubricating oil was one of the important things needed by the engine. Large temperature changes in the viscosity of lubricating oil would reduce the lubrication of engine parts, increase friction between metals, and cause engine parts to heat up quickly. Efforts to control this was by replacing mineral-based lubricating oils with environmentally friendly and biodegradable lubricating oil materials. The purpose of this study was to determine the effect of using a mixture of cooking oil and surfactants Polysorbate and Lecithin (2.5%, 5%, and 7.5%) as engine lubricants on the power and temperature produced by motorized vehicles. This research was quantitative experimental research. The dependent variables of this study were engine temperature and power. The control variables were a testing at room temperature, 4 stroke 125CC matic vehicle, and raw material using palm cooking oil. The test method used infrared thermo gun and Dyno test. The best result in this study was a mixture of cooking oil and Polysorbate 7.5%. It produced an average value of 2.98 HP at 6000 RPM engine speed, an average value of 7.02 HP at 7000 RPM engine speed, an average value of 6.99 HP at 8000 RPM engine speed, and an average value of 6.50 HP at 9000 RPM engine speed, with an average temperature value of 90.1ºC in which the temperature measurement results were still below the average value of oil temperature with a difference of 6.5ºC.